Kontrol Diri dengan Prokrastinasi Akademik pada Mahasiswa Fakultas Psikologi Universitas Negeri Makassar: Fatima Azzahrah, M. Ahkam Alwi, Andi Halima - Azzahrah, Fatima; Alwi, M. Ahkam; Halima , Andi (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2024)
Self-control or self-control is the ability of a student to organize, organize, guide, and direct behavior to achieve something. The purpose of this study was to determine the relationship between self-control and academic procrastination in students of the Faculty of Psychology, Makassar State University. Respondents in this study totaled 300 active student respondents at the Faculty of Psychology, State University of Makassar, batches of 2020, 2021 and 2022. The sampling technique used in this study was probability sampling with random sampling technique. The measuring instrument used is the procrastination assessment scale for students to measure the level of academic procrastination and the self-control scale to measure the level of self-control. The analysis technique used is the product moment correlation from Karl Pearson to see the relationship between self-control and academic procrastination. The results showed that there is a relationship between self-control and academic procrastination. It means that the higher the level of self-control, the lower the level of academic procrastination among students.